Estratégias de gestão na Atenção Primária à Saúde durante a pandemia de COVID-19 - Scarpa, Agatha (Universidade Federal de São Carlos, 2023)
Work in Primary Health Care was directly impacted by the COVID-19 pandemic, changing already consolidated practices and flows and requiring adaptation by the teams. Analyzing what was incorporated into the routine and brought improvements to the management process, from the perspective of managers, allows understanding the response to the challenges encountered in the reorganization of the work process and the adaptation of the Unified Health System to the pandemic context. Objective: understand the management strategies adopted by Primary Health Care managers during the COVID-19 pandemic. Method: this is a descriptive-exploratory study, with a qualitative approach, with data collection carried out in a Technical Health Supervision in the city of São Paulo. Two homogeneous focus groups were conducted online, with four and five participants respectively, through the Google Meet platform. Data were analyzed using the content analysis technique, based on the theoretical framework of the Health Work Process. All ethical aspects were respected. Results: The data obtained allowed the characterization of the managers' work process, whose purpose is to provide users with quality health care in line with the principles of the SUS. To this end, managers transform the health needs of users, as well as the needs for organization and management of work (object), through structured knowledge, various instruments, such as computers, telephones, software, reports, regulations, meetings, interactions social, among others. Although health work in PHC involves several agents, this research prioritized managers as an analysis perspective. Based on the understanding of the work process, the analysis allowed coding into three categories and respective subthemes (i) Challenges for management in the context of the COVID-19 pandemic: mediation of the unpredictable situation and its consequences and conflicting management levels and vertical decisions. (ii) Facilities for management in the context of the COVID-19 pandemic: teamwork and collaboration. (iii) Management strategies in the context of the COVID-19 pandemic: information and communication technologies and adaptation of access aiming for Universality and Equity. Conclusion: with the COVID-19 pandemic, managers incorporated technological strategies and innovations in the organization of work to facilitate the maintenance of care for users and their interface with the health unit team. Such strategies made it possible to overcome the challenges imposed at the time and tend to be incorporated into health services, given their power in the relationship between staff and users.
Management strategies in Primary Health Care during the COVID-19 pandemic
Keywords: Trabalho em saúde; Gestão em saúde; Atenção primária à saúde; COVID-19; Sistema único de saúde; Work in health; Health management; Primary health care; Unified health system; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA